Communication (Academy of Management Journal, 1963)
The article describes the author's experience working as a professor and head of the Commerce Department at the College of Arts, Science, and Technology in Kingston, Jamaica. An overview of the college's history and development as an organization and alternative educational opportunities are presented. A discussion is presented about the author's criteria for admission into programs offered in the commerce department and the variety of students from around the world seeking educational opportunities in Jamaica.